2019
DOI: 10.21608/bvmj.2019.17267.1096
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological studies on psychrotrophic bacteria and Pseudomonas isolated from frozen fish.

Abstract: Frozen fish are exposed to many risks of contamination during long chain of catching, transportation, dressing and freezing from different sources. Till they reach to consumers which make it harmful or unfit for human consumption. A total of 100 random samples of frozen Saurus and Mackerel (50 of each) were collected from different fish markets at El -Menofia governorate. They were subjected to bacteriological examination for isolation of Psychotropic and Pseudomonas species. The bacteriological examination re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…aeruginosa in broiler chickens in Egypt [ 41 ] whereas El-Tawab et al found that 34% of the tested frozen fish possessed P . aeruginosa [ 42 ]. Detection of P .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…aeruginosa in broiler chickens in Egypt [ 41 ] whereas El-Tawab et al found that 34% of the tested frozen fish possessed P . aeruginosa [ 42 ]. Detection of P .…”
Section: Discussionmentioning
confidence: 99%
“…The isolation rate of various water samples may fluctuate depending on the source and size of the sample, as well as the time and length of sample collection [3,37,40]. Previously, Algammal et al reported 28.3% prevalence of P. aeruginosa in broiler chickens in Egypt [41] whereas El-Tawab et al found that 34% of the tested frozen fish possessed P. aeruginosa [42]. Detection of P. aeruginosa in poultry and associated environment is alarming because of the possibilities of transmission of these pathogens to human.…”
Section: Plos Onementioning
confidence: 99%
“…The isolation rate of various water samples may fluctuate depending on the source and size of the sample, as well as the time and length of sample collection [3, 35, 39]. Previously, Algammal et al reported 28.3% prevalence of P. aeruginosa in broiler chickens in Egypt [40] whereas El-Tawab et al found that 34% of the tested frozen fish possessed P. aeruginosa [41]. Detection of P. aeruginosa in poultry and associated environment is alarming because of the possibilities of transmission of these pathogens to human.…”
Section: Discussionmentioning
confidence: 99%